Structure-activity relationships of 3-O-β-chacotriosyl oleanic acid derivatives as entry inhibitors for highly pathogenic H5N1 influenza virus. Issue 16 (15th August 2017) - Li, Sumei; Jia, Xiuhua; Shen, Xintian; Wei, Zhuwen; Jiang, Zhiyan; Liao, Yixian; Guo, Yiming; Zheng, Xiaojun; Zhong, Guohua; Song, Gaopeng
Graphical abstract: Highlights: A series of oleanane-type triterpenes were designed and synthesized. These compounds as H5N1 entry inhibitors exhibited strong inhibitory activity. Intensive SARs studies were conducted. Introduction of an oxo group to position 11 at OA can enhance the SI. Alteration of the C-3 configuration of OA can improve the selective index. Abstract: Highly pathogenic H5N1 virus (H5N1) entry is a key target for the development of novel anti-influenza agents with new mechanisms of action. In our continuing efforts to identify novel potential anti-H5N1 entry inhibitors, a series of 3- O -β-chacotriosyl oleanolic acid analogs have been designed, synthesized and evaluated as H5N1 entry inhibitors based on two small molecule inhibitors1 and2 previously discovered by us. The anti-H5N1 entry activities were determined based on HA/HIV and VSVG/HIV entry assays. Compound15 displayed the most promising anti-H5N1 entry activities with average IC50 values of 4.05 μM and good selective index (22.9). Detailed structure-activity relationships (SARs) studies suggested that either the introduction of an additional oxo group to position 11 at OA or alteration of the C-3 configuration of OA from 3β- to 3α-forms can significantly enhance the selective index while maintaining their antiviral activities in vitro . Molecular simulation analysis confirmed that the compounds exert their inhibitory activity through binding tightly to hemagglutinin (HA2) protein near the fusion peptide and prevent virus entry.